Geographic variation in the matching between call characteristics and tympanic sensitivity in the Weeping lizard - Antonieta Labra; Claudio Reyes‐Olivares; Felipe N. Moreno‐Gómez; Nelson A. Velásquez; Mario Penna; Paul H. Delano; Peter M. Narins (Ecology and Evolution, 2021)
Abstract Effective communication requires a match among signal characteristics, environmental conditions, and receptor tuning and decoding. The degree of matching, however, can vary, among others due to different selective pressures affecting the communication components. For evolutionary novelties, strong selective pressures are likely to act upon the signal and receptor to promote a tight match among them. We test this prediction by exploring the coupling between the acoustic signals and auditory sensitivity in Liolaemus chiliensis, the Weeping lizard, the only one of more than 285 Liolaemus species that vocalizes. Individuals emit distress calls that convey information of predation risk to conspecifics, which may respond with antipredator behaviors upon hearing calls. Specifically, we explored the match between spectral characteristics of the distress calls and the tympanic sensitivities of two populations separated by more than 700 km, for which previous data suggested variation in their distress calls. We found that populations differed in signal and receptor characteristics and that this signal variation was explained by population differences in body size. No precise match occurred between the communication components studied, and populations differed in the degree of such correspondence. We suggest that this difference in matching between populations relates to evolutionary processes affecting the Weeping lizard distress calls.